The Risk Management of P2P Online Lending Platforms in China-Take Lufax as An Example - Mao, Fangbin (2019)
The objective of the dissertation is to have an overall view of P2P lending platforms in China and put forward risk management suggestions after figuring out how they operate and what risks involved from the view of platforms. The paper mainly studies the risk management of P2P online platforms in China through literature review, regression analysis and case study. The paper first describes the development status of P2P in developed countries, especially the USA, and analyses the potential risks of P2P platforms in China via panel data regression and literature review. There are many risks involved and discussed in this paper, namely credit risk, liquidity risk, guarantee risk, operation risk and so on. After that, the risk management of Lufax is evaluated through the case study based on COSO-ERM model. The paper shows the potential risks involved in the process of P2P daily operation and summarizes the merits and disadvantages of Lufax P2P risk management. Finally, some suggestions are put forward to improve the risk management of P2P industry in China.